Liquid dosimeter with sensitivity in low-kGy range for the characterization of a new module for EB wastewater treatment - Schaap Lotte Ligaya; Teichmann Tobias; Poremba Andre; Besecke Joana Kira; Schopf Simone; Mattausch Gösta; von Hauff Elizabeth (Nukleonika, 2024)
In recent years, the use of low-energy electrons in various ecological and biotechnological applications has become increasingly relevant. One important application is the treatment of wastewater, wherein highly reactive species produced by water irradiation are used to oxidize pollutants. Low-energy electron irradiation has several advantages, such as minimal demands on radiation protection and electron beam (EB) source dimensions. However, to play into the main advantages of this technology and keep it economically viable, it is necessary to keep the absorbed dose as low as possible. This calls for a liquid dosimeter with sensitivity in the single digit kGy range. An extract from natural Hibiscus sabdariffa (Roselle) has been reported to show a radiochromic effect in this dose range. In the present work, Roselle dosimeter solutions were closely investigated and optimized to characterize a new module for EB wastewater treatment. Upon EB irradiation, the dosimeter solution demonstrated a dose-dependent fading in color, making it useful in the 0.3–7.5 kGy dose range.